2022
DOI: 10.1002/anie.202114167
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Receptor Mobility in Multivalent Binding on Lipid Membranes

Abstract: Numerous key biological processes rely on the concept of multivalency, where ligands achieve stable binding only upon engaging multiple receptors. These processes, like viral entry or immune synapse formation, occur on the diffusive cellular membrane. One crucial, yet underexplored aspect of multivalent binding is the mobility of coupled receptors. Here, we discuss the consequences of mobility in multivalent processes from four perspectives: (I) The facilitation of receptor recruitment by the multivalent ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 113 publications
0
27
0
Order By: Relevance
“…A low spatial tolerance decreases the conformational and combinatorial entropy penalties. 33 On the contrary, the higher conformational possibilities given by the linkers increases the entropic penalty of binding. The third effect may derive from a combination of the previous two, indicating that the observed average effect comes from a mixture of specific and nonspecific activation stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low spatial tolerance decreases the conformational and combinatorial entropy penalties. 33 On the contrary, the higher conformational possibilities given by the linkers increases the entropic penalty of binding. The third effect may derive from a combination of the previous two, indicating that the observed average effect comes from a mixture of specific and nonspecific activation stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that reduced flexibility confers an advantage for the thermodynamics of ligand binding. A low spatial tolerance decreases the conformational and combinatorial entropy penalties . On the contrary, the higher conformational possibilities given by the linkers increases the entropic penalty of binding.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 Local high concentrations can temporarily be locked in place through changes in surrounding lipid dynamics. 20,49,58 From the receptor side, the boundary conditions for MPR and more general superselective multivalent interactions can be easily reached. As many natural ligands are present on precisely organized scaffolds, as in the case of viruses and geometric toxin complexes, 2,59 MPR is likely to be omnipresent in molecular biology.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 T h i s c o n t e n t i s Within a functional interaction complex in nature, the numbers of ligands and receptors are often low-to-moderate and their position in space can be (temporally) controlled. 20 Spatial organization of ligands is typically observed in pathogens (viruses), and our immune system is highly developed to recognize such patterns. 21 In microbiology, a classical welldefined system is seen in the multivalent interaction between the bacterial phages and their target receptor used in phage display.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The trends in binding efficacy observed across RGD scaffolds in function of α 5 β 1 in extended conformation can be explained as a trade-off in terms of the following: (i) a match of inter-receptor spacing to ligand presentation, (ii) number and density of integrins within a cluster [ 10 ] (iii) local cluster topography due to thickness of glycocalyx [ 58 ] (iv) potential binding sites per surface area probed (v) entropic penalty vs. enthalpic gain in scaffold binding through relatively rigid ligand presentation [ 59 , 60 ]. To elaborate on the complexity in the interpretation of the binding trends observed in terms of trade-off between glycocalyx thickness and enthalpy-entropy compensation, a thicker glycocalyx increases integrin-mediated cell adhesion by entrapment in an activated state once extended from the cell surface [ 61 ].…”
Section: Discussionmentioning
confidence: 99%